Strategi Bauran Pemasaran Grand City Hall Hotel Medan dalam Meningkatkan Kunjungan Tamu pada Saat Pandemi - Liyushiana Liyushiana (Politeknik Pariwisata Medan, 2022)
The pandemic has had a huge impact on the hotel sector, so hotels need to prepare various strategies, at least to survive. The purpose of this study was to describe what strategies were taken by the Grand City Hall Hotel Medan in dealing with the pandemic. The approach taken in achieving the objectives of this research is a marketing mix strategy with the 7P concept (product, price, people, promotion, place, physical evidence and process). The methodology of this research is qualitative where data collection is done by interview and observation method. The results of the study show that several marketing strategies that play a major role in maintaining operations at Grand City Hall Medan are: promotions that are continuously carried out through various platforms, especially social media; pricing that adjusts to circumstances, setting rules on uniform use that adapts health protocol policies, and adjusting service processes according to CHSE rules.